Penguatan Karakter Melalui Pendidikan Islam Di Tk Mawaddah Kota Banjarmasin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2013)
Penelitian ini menggunakan metode kualitatif, bertujuan untuk mengungkapkan motede pembelajaran dan strategi penguatan karakter anak didik melalui pendidikan Islam. Dari penelitian ini diungkapkan, bahwa sejak berdiri taman kanak-kanak ini konsisten menginternalisasikan nilai-nilai pendidikan Islam kepada anak didik sebagai pondasi penguatan karakter. Dengan metode pembelajaran Beyond Centers and Circle Time. Metode ini sangat relevan kebutuhan anak didik, yaitu dunia bermain, sehingga memperlancar proses pembelajaran. Sedangkan strategi penguatan karakter dilakukan melalui proses panjang dan berkesinambungan dalam menginternalisasikan nilai-nilai pendidikan Islam melalui pengenalan, pembiasaan dan keteladanan yang didukung kemampuan orangtua mendidik anak yang diperoleh melalui kegiatan parenting class.Â This study aims to reveal: 1) an overview of Mawaddah kindergarten, 2) the learning method of Mawaddah kindergarten and 3) the developing strategies to strengthen the character of the students through Islamic education. This study uses qualitative methods; the data was collected through interviews, observation and documentation. The results show that since Mawaddah kindergarten was established, it has been consistent in teaching the values of Islamic education in the belief that these values will become a solid foundation to strengthen studentsâ€™ character. The â€œBeyond Centers and Circle Timeâ€ method, which is known as sentra method, appears to be very relevant to the needs of childrenâ€”fun. The strategy of strengthening character does not stop there. It continues in the family with supports for parentsâ€™ ability to educate children through parenting classes. Strengthening character cannot be accomplished in an instant; it can only be accomplished through a long and continuous process using the values of Islamic education through introduction, habituation and positive examples.
Keywords: Karakter; Pendidikan Islam; Anak Usia Dini; Character; Islamic Education; Early Childhood.